2009
DOI: 10.1007/s00216-009-3306-7
|View full text |Cite
|
Sign up to set email alerts
|

Zymographic assay of plant diamine oxidase on entrapped peroxidase polyacrylamide gel electrophoresis. A study of stability to proteolysis

Abstract: A zymographic assay of diamine oxidase (DAO, histaminase, EC 1.4.3.6), based on a coupled peroxidase reaction, and its behavior at proteolysis in simulated gastric and intestinal conditions, are described. The DAO activity from a vegetal extract of Lathyrus sativus seedlings was directly determined on sodium dodecyl sulfate polyacrylamide electrophoretic gels containing entrapped horseradish peroxidase, with putrescine as substrate of histaminase and ortho-phenylenediamine as co-substrate of peroxidase. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In order to further identify the protein profiles, samples of free DAO and of DAO extracted from microspheres were run in SDS‐PAGE under nonreducing conditions for protein staining and for zymography. Previous studies indicated the presence of a single band at 72 kDa in denaturating SDS‐PAGE for vegetal DAO extracted from L. sativus and a band at 95 kDa for DAO extracted from Pisum sativum L . The molecular mass of pea seedling amine oxidase was also investigated using the method of gel filtration, indicating a value of 184.0 ± 2.6 kDa .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to further identify the protein profiles, samples of free DAO and of DAO extracted from microspheres were run in SDS‐PAGE under nonreducing conditions for protein staining and for zymography. Previous studies indicated the presence of a single band at 72 kDa in denaturating SDS‐PAGE for vegetal DAO extracted from L. sativus and a band at 95 kDa for DAO extracted from Pisum sativum L . The molecular mass of pea seedling amine oxidase was also investigated using the method of gel filtration, indicating a value of 184.0 ± 2.6 kDa .…”
Section: Resultsmentioning
confidence: 99%
“…Our uncoated microspheres have been investigated in SGF and SIF in order to evaluate the physicochemical properties of the CaCMS/alginate complex. Previous studies showed that free DAO is sensitive to gastric acidity . It is also known that alginate microspheres (with porous structure) allow the diffusion of gastric acidity into microspheres inducing a rapid inactivation of enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, DAO is mainly located in the intestines, placenta and kidneys [6,11]. Intestinal DAO acts as a protective barrier against exogenous histamine, especially of food origin [12][13][14]. A deficiency of DAO enzyme may thus lead to excess the normal plasmatic levels of histamine (0.3 -1.0 ng/mL) and the subsequent appearance of histamine intolerance symptoms [15,16].…”
Section: Introductionmentioning
confidence: 99%